Remembering rest periods in law: another tool to limit excessive working hours - Ghosheh, Naj (Geneva, 2016)
"Research on working time legislation exists, but little has been done to examine the specific provisions about rest periods in and how they can supplement national working time legislation.1 This paper seeks to fill this lacuna. First, it will examine national legislation on weekly working hour limits and identify some key issues that affect a worker’s ability to get rest. Subsequently, it will examine the specific provisions on rest periods in international standards and national legislation, focusing on four key areas: rest periods during the work day, daily rest, weekly rest, and annual leave. It will then conclude with some final observations."